2018
DOI: 10.1007/s11356-018-2371-x
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of energy reserves and biometry as potential tools for assessing the effects of pest management strategies on the earwig, Forficula auricularia L

Abstract: Apple orchards are heavily treated crops and some sprayed insecticides are recognized to have toxic effects on non-target arthropods. Earwigs are important natural enemies in pip-fruit orchards and contribute to the biological control of aphids. In addition, due to their ease of capture and identification, they are an interesting potential bioindicator of the possible detrimental effects of different orchard management strategies. In this study, we measured the energy reserves and some morphological traits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Our previous study reported contrasting results for measurements on earwigs sampled in the same orchards in July. In that latter study, earwigs from organic orchards were the heaviest and females were lighter than males (Suchail et al, 2018).…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Our previous study reported contrasting results for measurements on earwigs sampled in the same orchards in July. In that latter study, earwigs from organic orchards were the heaviest and females were lighter than males (Suchail et al, 2018).…”
Section: Discussionmentioning
confidence: 77%
“…A single person carried out all measurements to avoid user bias. For adults (males and females) and nymphs, we measured the maximum width of the prothorax, inter-eye and telson and the length of the left femur of the third pair (Suchail et al, 2018). The growth of earwig nymphs was assessed through the increase in body weight, femur length and prothorax width by calculating the ratio between two successive life-stages (N4/N3 or adult/N4).…”
Section: 4morphometric Measurementsmentioning
confidence: 99%
See 3 more Smart Citations